High-intensity statin therapy in patients with chronic kidney disease: a systematic review and meta-analysis. Issue 5 (15th May 2015) - Yan, Yu-Ling; Qiu, Bo; Wang, Jing; Deng, Song-Bai; Wu, Ling; Jing, Xiao-Dong; Du, Jian-Lin; Liu, Ya-Jie; She, Qiang
Abstract : Objective: To evaluate the efficacy and safety of high-intensity statin therapy in patients with chronic kidney disease (CKD). Design: A systematic review and meta-analysis. Data sources: Randomised controlled trials (RCTs) comparing high-intensity statin therapy (atorvastatin 80 mg or rosuvastatin 20/40 mg) with moderate/mild statin treatment or placebo were derived from the databases (PubMed, Embase, Ovid, the Cochrane Central Register of Controlled Trials (CENTRAL) in the Cochrane Library, and ISI Web of Knowledge). Outcome measure: Primary end points: clinical events (all-cause mortality, stroke, myocardial infarction and heart failure); secondary end points: serum lipid, renal function changes and adverse events. Results: A total of six RCTs with 10 993 adult patients with CKD were included. A significant decrease in stroke was observed in the high-intensity statin therapy group (RR 0.69, 95% CI 0.56 to 0.85). However, the roles of high-intensity statin in decreasing all-cause mortality (RR 0.85, 95% CI 0.67 to 1.09), myocardial infarction (RR 0.69, 95% CI 0.40 to 1.18) and heart failure (RR 0.73, 95% CI 0.48 to 1.13) remain unclear with low evidence. High-intensity statin also had obvious effects on lowering the LDL-C level but no clear effects on renal protection. Although pooled results showed no significant difference between the intervention and control groups in adverse event occurrences, it was still insufficient to put off the doubts that high-intensity statin might increase adverse events because of limited data sources and low quality evidences. Conclusions: High-intensity statin therapy could effectively reduce the risk of stroke in patients with CKD. However, its effects on all-cause mortality, myocardial infarction, heart failure and renal protection remain unclear. Moreover, it is hard to draw conclusions on the safety assessment of intensive statin treatment in this particular population. More studies are needed to credibly evaluate the effects of high-intensity statin therapy in patients with CKD.